2018
DOI: 10.4018/ijom.2018070101
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Egyptian Consumers' Intentions in Online Shopping

Abstract: The purpose of this article is to investigate the factors that impact on Egyptian consumers' attitudes and intentions to use online shopping by integrating the technology acceptance models of Davis, and Fishbein and Ajzen's theory of reasoned action. In addition, other variables will be added such as trust and perceived enjoyment for its theoretical framework. A total 306 current internet users in Egypt provided usable responses. Structural equation modelling was employed to test the proposed model and researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 66 publications
4
6
1
1
Order By: Relevance
“…This research also showed that in different consumer segments, there exist factors that directly influence consumers' behavioral intention to shop online. In contrast to prior study (Cha, 2011;Elseidi, 2018), perceived enjoyment was found to be a predictor of online shopping intention only in Suspicious Browsers and Incompetent Consumers segments. Unlike the findings of Wu et al (2007) and Agag and El-Masry (2016), perceived compatibility of online shopping with consumers' existing lifestyle was found to be a significant predictor of online shopping intention only in Suspicious…”
Section: Theoretical Implicationscontrasting
confidence: 99%
See 4 more Smart Citations
“…This research also showed that in different consumer segments, there exist factors that directly influence consumers' behavioral intention to shop online. In contrast to prior study (Cha, 2011;Elseidi, 2018), perceived enjoyment was found to be a predictor of online shopping intention only in Suspicious Browsers and Incompetent Consumers segments. Unlike the findings of Wu et al (2007) and Agag and El-Masry (2016), perceived compatibility of online shopping with consumers' existing lifestyle was found to be a significant predictor of online shopping intention only in Suspicious…”
Section: Theoretical Implicationscontrasting
confidence: 99%
“…These findings are consistent with the studies which highlight the important role of PU (Agag & El-Masry, 2016;Bigné-Alcaniz et al, 2008;M. Y. Chen & Teng, 2013;Elseidi, 2018;Fortes & Rita, 2016;S. Ha & Stoel, 2009;Pelaez et al, 2019), compatibility (Agag & El-Masry, 2016;Al-Ajam & Nor, 2013;Eri et al, 2011;Vijayasarathy, 2004), and PSP (Dwivedi et al, 2017;H.…”
Section: Theoretical Implicationssupporting
confidence: 92%
See 3 more Smart Citations